(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The content of the lessons “National Independence Ideology and the Foundations of Spirituality” and “History of Pedagogy” contributes to the development of moral and human behavior of students and pupils. It has become possible to enrich knowledge about the essence of the preventive work being carried out in our Republic to study the prevention of security threats associated with the use of regional mass media in Central Asia. The article reflects: the theoretical basis for researching regional security in Central Asia, revealing the historical roots of emerging ideological and ideological threats, demonstrating the manifestations of ideological and ideological threats directed at Central Asia, illuminating the process of forming policies to combat ideological and ideological threats in Central Asian states, as well as Uzbekistan’s cooperation with international organizations in combating ideological and ideological threats.